Extended Reality as a training approach for visual real-time feedback in golf - Geisen, Mai; Nicklas, Andre; Baumgartner, Tobias; Klatt, Stefanie (IEEE transactions on learning technologies, 2024)
Visual feedback can enhance motor learning in golf, however, so far, this has mostly been time-delayed. Using Extended Reality (XR), learners can receive visual feedback in real-time without relying on an external perspective. The aim of this study was to investigate a novel XR-based method of real-time feedback for golf putt training. Thirty-two subjects were divided between a XR-group and a technique instruction (TI) training group, completing three weeks of training each, and a no-training control (NTc) group. XR training included a virtual club projected into the real training environment via HoloLens 2. Real-time information was provided on the pre-calculated targeted club alignment and velocity. The TI method included written technical instructions already used in golf putt training. Before and after the training, all subjects performed a pre-, post- and retention-test, and two transfer-tests with shorter (2 m) and longer (4 m) putting distances than during training (3 m). Results showed a significant increase in the number of hits and a significant decrease in the radial error after training in all groups. The number of hits remained the same during the retention-test and at shorter putting distance, but decreased at longer distance. The radial error decreased even more during the retention-test and revealed no difference between putting distances. Our study shows that the acquisition of golf putting skills can be enhanced not only through a proven technique instruction training, but also by incorporating visual real-time feedback via XR. Future studies could examine the extent to which the effects of this method exceed those of technique instruction training over a longer period when learners can familiarize themselves with it more.